Metaphoric gestures and viewpoint in coming out narratives: a frame-level analysis - Dyrmo, Tomasz (Studia Anglica Posnaniensia, 2025)
The present study investigates viewpoint phenomena in metaphoric gestures in coming out narratives at the level of frames. It aims to answer the questions of whether there is any correlation between a given semantic frame (volitional coming out / being forced to come out) and the viewpoint taken in a metaphoric gesture (either observer or character viewpoint). Additionally, this paper aims to present a qualitative analysis of selected examples from a dataset to show how viewpoint can be expressed gesturally. So far, the topic of viewpoint in gestures has been extensively researched in the context of iconic gestures, and ample space remains for analyses of viewpointed metaphoric gestures. For the present analysis, 32 videos taken from YouTube were used, 749 gestures were found, with 363 of them being metaphoric. To the quantitative end, the results from the analysis do not show any relationship between the semantic frames and types of viewpoints.